Rancang Bangun Aplikasi Penjualan pada Apotek Sentra Berkat Surabaya - Naniek, Lay; Sulitiowati, Sulitiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Sentra Berkat Pharmacy is commercial enterprise engaged in the sale of medicines and medical support items such as masks, bandages, oxygen, bedpans and others. Sales made in two ways: using a prescription and without a prescription. Sentra Berkat Pharmacy received retail sales and wholesales. Broadly speaking, the problems that often occur in Sentra Berkat Pharmacy included difficulty collection of goods, the sales data for all processes based manual. Pharmacy is also difficult to determine the condition of the inventory (inventory) of goods in real time. Accounts receivable collection procedures Sentra Berkat Pharmacy also have constraints in terms of charging overdue. The author makes this project by conducting a survey, noting the process is in the form of document flow as help make the development process and program. The process developed is not a complete transformation, but repairs. The author makes computer-based sales application as a solution to record sales data, data items including expiry, and record all transactions that occur, and good reports. The results of this development project includes the maintenance of master data (item, suppliers, customers, users), goods receipt transactions, sales transactions and settlement of accounts receivable transactions. These applications can allow users to keep records of all transactions and billing more accurate and faster.